Individual Meaning-Centered Psychotherapy for palliative cancer patients in Lithuania. A case report - Sutkevičiūtė, Meda; Stančiukaitė, Monika; Bulotienė, Giedrė (Acta medica Lituanica, 2017)
Patients with oncological diseases, especially palliative care patients, suffer from physical and psychological difficulties. The quality of life of such patients is bad, they do not have purpose to live and they feel anxiety and distress. In 1959 Victor Frankl wrote the book Man’s Search for Meaning in which he stated that the driving force of human life lay in the ability to discern the  meaning of faith and spirituality. Inspired by Frankl’s ideas, the American psychiatrist William Breitbart with colleagues have developed both an individual and group model of Meaning-Centered Psychotherapy. Studies show that this therapy helps patients to cope with distress, to discover the  meaning of life in palliative care patients, and to find the  strength to look at life positively; also, it relieves the  symptoms of illness. The  Meaning-Centered Psychotherapy is integrated in various countries and has recently been initiated for palliative patients in Lithuania. The individual Meaning-Centered Psychotherapy was used in the case reviewed in this paper.
Keywords: palliative patients; oncology; psychotherapy; meaning